الاحتراق النفسي لدى معلمي صعوبات التعلم: دراسة تطبيقية في سلطنة عمان - Salem Albusaidi, A.S.; Awang Mat Dahan, H.B. (Universiti Sains Islam Malaysia, 2024)
When teachers communicate with the students of learning difficulty continuously, this consumes their strength and abilities and leads to continuous pressure. Therefore, the teacher will feel weakness achievement and as a consequence will cause depression, worries and nervousness. This study aimed to reveal the fact how much psychological combustion is happening among teachers of learning difficulty and discuss the reasons of the phenomenon. The descriptive method followed. The communities of the study are teachers of learning difficulty at schools of: Muscat and Al Batinah. The questionnaires were given to a random sample of (29) teachers. The findings were: the total response of all paragraphs was (fine) and it has reached (3) which points to psychological combustion among teachers of learning difficulty. The response percentage among teachers with experience (11 years and above) was more than those who have experience from (1-5) which means that teachers with more experience are exposed to psychological combustion. Indeed, the reasons behind the psychological combustion are attributed to weakness in the acdmeic preparation in term of school guidance; also, the school administration which always blame teachers in every problem occur between the teachers and the students causes increasing the phenomenon.